IDENTIFIKASI SIFAT FISIK TANAH ALIH FUNGSI LAHAN HUTAN MENJADI PERKEBUNAN KAKAO (Theobroma cacao L.) DI DESA PARIGIMPUâU KECAMATAN PARIGI BARAT KABUPATEN PARIGI MOUTONG - Jasmin, Sutrisno; Ramlan, Ramlan; Monde, Anthon (AGROTEKBIS, 2017)
This study aims to determine the physical properties of the soil to convert forest into plantations of cacao (Theobroma cacao L.) in the village of Parigimpuu District of West Parigi district, Parigi Moutong. Soil analysis carried out in the Laboratory of Soil Science Unit of the Faculty of Agriculture, University Tadulako. The method used in this research field survey by reviewing and determining the location and make the determination of the location of the observation sample points on each land use (forests and cacao plantations) and followed by soil sampling to analysis in the laboratory. Soil sampling is not intact with depth (0-20) cm of topsoil and soil intact by using the sample ring. On forest land conducted soil sampling at three different points, each point in kompositkan on the ground is not intact and cocoa land in 3 different locations, where the first location has 3 points, so that the number of soil samples intact gained as much as 12 samples and the land is not intact as much as 3 samples. The results showed changes in soil physical properties of each land use (forests and cacao plantations) Bulk Density varies greatly with relatively mild, moderate and severe. Permeability fast to very fast. Porosity from bad to good. Soil texture on forest land dominated sand fraction, relatively low organic C difference causes Â Â Â Â Â Â Â Â a change in the physical properties of the soil. Key Words: Forest land, Cocoa land, Soil Physical Properties.